Screening of plants from diversified natural grasslands for their potential to combine high digestibility, and low methane and ammonia production. (21st July 2014) - Macheboeuf, D.; Coudert, L.; Bergeault, R.; Lalière, G.; Niderkorn, V.
<x content-type="archive" xml:space="preserve">Abstract</x> A total of 156 plant species from 35 botanical families collected from diversified grasslands in the French Massif Central were screened in vitro for their potential to combine high nutritive value for ruminants and a reduced impact on the environment. The vegetative part of plants were analyzed for their chemical composition and incubated in a batch system containing buffered rumen fluid at 39°C for 24 h. The gas production and composition were recorded, and the fermentation end-product concentrations in the incubation medium and the in vitro true organic matter digestibility (IVTOMD) were determined. The results were expressed relative to perennial ryegrass (PRG) values used as a reference. We observed that no relationship between methane (CH4) and volatile fatty acids (VFA) was evidenced for 12 plants, the fermentation of these plants producing significantly less CH4 for a similar level of VFA production. In all, 13 plants showed 50% less CH4 production per unit of organic matter truly digested (OMTD) than PRG. Among these plants, two reduced CH4 by more than 80% and four species had an IVTOMD higher than 80%. The underlying modes of action seem to be different among plants: some result in an accumulation of H2 in the fermentation gas, but others do not. In terms of nitrogen (N) use efficiency, the fermentation of 37 plants halved the ratio between ammonia (N–NH3) and plant N content compared with PRG, of which six showed a complete absence of N–NH3 in the medium. Among these plants, four maintained the IVTDMO at values not significantly different from PRG (P>0.05). Considering the multi-criteria selection, 16 plants showed simultaneously a reduction of more than 80% in N–NH3 production and 30% in CH4 emission per unit of OMTD compared with PRG, including three with an IVTOMD higher than 80%. Overall, the botanical families that reduced simultaneously CH4 and N–NH3 most efficiently were the Rosaceae, Onagraceae, Polygonaceae and Dipsacaceae. The Onagraceae also gave high values for IVTOMD.